Harmonic Mitigation in Traction Supply Substation Using Cascaded H-Bridge Converter - A. Awalludin; C. L. Toh (Institute of Advanced Engineering and Science, 2018)
The conventional three-level inverter has been proposed to act as a recuperating converter in Traction Supply Substation. This converter is mainly used to feed back the regenerative braking energy to the grid. However, passive filter is desired to mitigate the current and voltage harmonics. Therefore, this paper investigates the possibility to use a seven-level Cascaded H-Bridge (CHB) converter as the recuperating converter without additional filtering. The proposed converter is modeled with MATLAB/Simulink simulation software. It is then simulated with two potential modulation schemes, namely Phase-Shifted PWM (PS-PWM) and Phase-Disposition PWM (PD-PWM). The quality of AC waveforms produced by these two modulation methods is compared and studied. The results show that PS-PWM technique is preferable for this application as it offered a clean AC current waveform with less than 5% harmonic distortion. However, a twenty-one-level CHB was predicted to comply with the 8% voltage harmonic requirement.